Obesity and trauma mortality: Sizing up the risks in motor vehicle crashes. Issue 1 (January 2017) - Joseph, Bellal; Hadeed, Steven; Haider, Ansab A.; Ditillo, Michael; Joseph, Aly; Pandit, Viraj; Kulvatunyou, Narong; Tang, Andrew; Latifi, Rifat; Rhee, Peter
Summary: Background: Protective effects of safety devices in obese motorists in motor vehicle collisions (MVC) remain unclear. Aim of our study is to assess the association between morbid obesity and mortality in MVC, and to determine the efficacy of protective devices. We hypothesised that patients with morbid obesity will be at greater risk of death after MVC. Methods: A retrospective analysis of MVC patients (age ≥16 y.o.) was performed using the National Trauma Data Bank from 2007 to 2010. Patients with recorded comorbidity of morbid obesity (BMI ≥ 40) were identified. Patients dead on arrival, with isolated traumatic brain injury, or incomplete data were excluded. The primary outcome was in-hospital mortality. Multivariate logistic regression was performed. Results: Our sample of 214, 306 MVC occupants included 10, 260 (4.8%) morbidly obese patients. Mortality risk was greatest among occupants with morbid obesity (ORcrude 1.74 [1.54–1.98]). After adjusting for patient demographics, safety device and physiological severity, odds of death was 1.52 [1.33–1.74] times greater in motorists with morbid obesity. Motorists with morbid obesity were at greater risk of death if no restraint (OR 1.84 [1.47–2.31]), seatbelt only (OR 1.48 [1.17–1.86]), or both seatbelt and airbag were present (OR 1.49 [1.13–1.97]). No significant differences in the odds of death exist between drivers with morbid obesity and non-morbidly obese drivers with only airbag deployment (OR 0.99 [0.65–1.51]). Conclusions: Motorists with morbid obesity are at greater risk of MVC. Regardless of safety device use, occupants with morbid obesity remained at greater risk of death. Further research examining the effectiveness of vehicle restraints in drivers with morbid obesity is warranted.